Concept marriage in the artistic heritage of Olga Kobylyanska (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article discusses the features of artistic realization of the concept of marriage in the artistic heritage of Olga Kobylyanska. The focus is on the disclosure paradigm of marriage, their place in the system of values of characters of different works of writer and feminist context of ideas. The author examines different models of family relations and interpreted their role in the harmonization of being a person.
Keywords: concept; the female character; marriage; feminism; modernism